Ship receipt from April 2, 1856 (2023)
Thayer's receipt for passage on the ship S. S. Hermann, dated April 2 1856. This receipt documents Thayer's return trip to America on the wooden side-paddle steamer S. S. Hermann, which departed Bremen in early April 1856; he arrived at the Port of New York on Thursday, May 8.